Biological features, biotechnology, cultivation and areas of stagnation of microscopic single-cell algae of the genus Chlorella: (review of the literature) - V. Grishko; V. Zotsenko; N. Bogatko; D. Ostrovskiy (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Гжицького. Серія: Сільськогосподарські науки)
Currently, microscopic algae have become a promising alternative raw material that represents a huge biodiversity and has many advantages that can approach the potential of traditional agricultural raw materials. The article describes a wide range of properties of the microalgae Chlorella vulgaris and Chlorella sorokiniana based on scientific studies reported in various literature sources. Attention is focused on their morphology, physiology, and modern biotechnological approaches to the cultivation, accumulation, collection, purification, and processing of biomass are considered. The processes of obtaining valuable biologically active components, such as proteins, lipids, carbohydrates, and pigments from the microalgae Chlorella vulgaris and Chlorella sorokiniana are presented. Particular attention is paid to the influence of cultivation conditions on the chemical composition of the obtained microalgal biomass, as well as methods and technologies for its further processing into valuable biologically active components. The article describes the use of Chlorella microalgae in such industries as biotechnology, pharmaceuticals, cosmetics, food and chemicals, energy, and agriculture. The article emphasizes the prospects of microalgae in the production of biofuels, including biodiesel and bioethanol, as well as in bioremediation, including wastewater treatment. Based on global scientific research, Chlorella microalgae have been shown to be multifunctional sources of proteins, lipids and carbohydrates suitable for both human consumption and animal feed. Due to the ability of microalgae to grow in different environmental conditions, they are a promising solution for industrial biomass production, which is potentially unable to compete with traditional farming methods. Thanks to its ability to use carbon dioxide and release oxygen in the process of life, the concentration of CO2 in the environment is reduced, which in turn is of crucial environmental importance. The authors emphasize the significant scientific and technological progress in the use of microalgae Chlorella vulgaris in recent years, due to its versatility and significant opportunities for further research and practical application in various fields.